2018
DOI: 10.1029/2018ja025376
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Complex Two N‐Wave Ionospheric Signature of the 2016 Kaikoura Earthquake

Abstract: Major earthquakes (>∼6.5 Mw) can generate observable waves which propagate not only through the Earth but also through the Earth's ionosphere. These traveling ionospheric disturbances can be observed using multifrequency GPS receivers to measure the ensuing perturbations in the Total Electron Content of the ionosphere. Assisted by a statistical approach we developed to indicate the occurrence of a significant TEC perturbation from the normal background behavior, we detect a traveling ionospheric disturbance ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…A strong second packet arrives shortly after, due to prior reflection. Similar waveforms were reported above the weaker 2016 Kaikoura EQ (Li et al, ), where leading nonlinear waves were observed before a weaker, trailing packet; the dominant features of these signatures may be explained simply by dispersion, steepening, and reflection (see Figures 7 and 9 of Zettergren et al, ).…”
Section: Resultssupporting
confidence: 78%
“…A strong second packet arrives shortly after, due to prior reflection. Similar waveforms were reported above the weaker 2016 Kaikoura EQ (Li et al, ), where leading nonlinear waves were observed before a weaker, trailing packet; the dominant features of these signatures may be explained simply by dispersion, steepening, and reflection (see Figures 7 and 9 of Zettergren et al, ).…”
Section: Resultssupporting
confidence: 78%
“…CSID can be detected in the vicinity of an earthquake's epicenter but also up to 6,000–8,000 km away from it. The near‐field CSID represent ionospheric response to acoustic waves generated directly by coseismic vertical crustal displacements (e.g., Afraimovich et al, ; Afraimovich et al, ; Afraimovich et al, ; Astafyeva & Heki, ; Cahyadi & Heki, ; Calais & Minster, , ; Heki & Ping, ; Jin et al, ; Komjathy et al, ; Li et al, ; Lognonné et al, ; Zettergren & Snively, ). The far‐field CSID are usually associated with the propagation of the Rayleigh surface waves (Astafyeva et al, ; Ducic et al, ; Kakinami et al, ; Liu, Tsai, Ma, et al, ; Rolland et al, ; Jin et al, ) or of the air surface waves (Astafyeva & Afraimovich, ; Liu, Tsai, Chen, et al, ).…”
Section: Ionospheric Response To Earthquakes and Tsunamismentioning
confidence: 99%
“…Several studies reported the characteristics of TEC perturbations generated by coseismic IAWs during the Kaikoura earthquake (Bagiya et al., 2018; Lee et al., 2018; Li et al., 2018). We reanalyze observed CIDs, particularly for the purposes of model result validation and to test hypotheses on the Papatea fault evolution.…”
Section: The 2016 M78 Kaikoura Earthquakementioning
confidence: 99%